Science Fiction by, about, and for Arabs: Case Studies in De-Orientalising the Western Imagination. (1st October 2020) - Aysha, Emad El-Din
Abstract : Orientalism is a much maligned concept. While geared to the service of the Western colonial sense of superiority, Orientalism is, at base, a loose set of symbols and motifs that is more geared towards an introspective critique of the West itself. It represents certain internal antagonisms and Western anxieties that emerge in confrontations with the East over gender and sexuality. This becomes evident when it comes to Western science fiction (written and filmed) among other popular genres and specifically when applied to Arabs and Muslims (the "classical" East). Hitherto, most literature on the Orientalism evident in Western SF has focused on the Far East, via Techno-Orientalism and Cyber-Punk. The growing strength of Arab and Muslim SF, however, can counter these Orientalist tendencies in the genre; taking Egyptian SF as a test case. Western SF, moreover, can set its own house in order in the meantime, since SF allows for symbolic substitutes to existential threats traditionally posed by the East in the Western imagination.